The Impact Of Tiktok Social Media Usage, Fear Of Missing Out (Fomo) Behavior, And Financial Literacy On Personal Financial Management Among UNPAB Management Students Of The 2022 Cohort - Samosir, Gresia; Pramono, Cahyo; Ardian, Noni (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the influence of TikTok social media, Fear of Missing Out (FoMO) behavior, and financial literacy on personal financial management among Management students of Universitas Pembangunan Panca Budi (UNPAB), Class of 2022. This research employs a quantitative approach using a survey method. The population of this study consists of 352 Management students of UNPAB Class of 2022, with a sample of 77 respondents determined using the Slovin formula with a 10% margin of error. Data were collected through questionnaires measured using a Likert scale and analyzed using multiple linear regression analysis with the assistance of statistical software. The results show that partially, TikTok social media and financial literacy have a positive and significant effect on students’ personal financial management, while Fear of Missing Out (FoMO) does not have a significant effect. Simultaneously, TikTok social media, Fear of Missing Out (FoMO), and financial literacy have a significant effect on the personal financial management of Management students at UNPAB Class of 2022. These findings indicate that the positive use of social media and a high level of financial literacy play an important role in shaping students’ personal financial management behavior.